7-AMINOCEPHALOSPORANIC ACID – PRODUCTION AND SEPARATION - TUCALIUC, Alexandra; POȘTARU, Mădălina; CAȘCAVAL, Dan; GALACTION, Anca-Irina (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Cephalosporins, a large group of β-lactam antibiotics, contain a 7-aminocephalosporanic acid (7-ACA) nucleus which is derived from cephalosporin C, and substitutions of chemical groups or modifications of 7-ACA side-chains resulting in varying pharmacologic properties and antimicrobial activities, development of useful antibiotic agents, also. Cephalosporin C obtained by fungus fermentation can be transformed to 7-ACA by two-step or one step enzymatically conversion process. The most important step in 7-ACA downstream process is represented by its separation from enzymatically produced reaction mixture. Among the used methods new separation techniques have been developed and applied to bioseparations, like reactive extraction and pertraction which have considerable potential.